Pengaruh Model Process Oriented Guided Inquiry Learning terhadap Keterampilan Berpikir Kritis Siswa dalam Pembelajaran Geografi di SMA Negeri 1 Singaraja - Maretanta Ananda Pinasthi; I Putu Sriartha; Ida Bagus Made Astawa (Journal on Education, 2024)
The study’s objectives were to: (1) describe how the Process Oriented Guided Inquiry Learning (POGIL) model was utilized in teaching geography to students at SMA Negeri 1 Singaraja, (2) analyze the variation in students’ critical thinking abilities before and after POGIL’s implementation in their geography studies, (3) analyze the impact of the POGIL onenhancing students' critical thinking in geography learning. Employing a quasi-experimental design, subjects were divided into experimental and control groups through random selection post-equality testing. ata collection involved observations, document reviews, and test. Analysis included qualitative descriptions and inferential statistics using t-tests. The results of the research is: (1) effective execution of POGIL in geography education by the teacher, (2) a boost in the experimental group students’ critical thinking compared to the control group, (3the study revealed significant disparities in students’ critical thinking skills when comparing geography education utilizing the POGIL model to traditional teaching methods. This shows that the Process Oriented Guided Inquiry Learning model has a significant effect on improving students' critical thinking skills in geography learning.